Ellagic acid could prevent experimentally induced oxidative stress in rats - Mehmet Ali Kisacam; Gonca Ozan Kocamuftuoglu; Enver Ozan; Sema Temizer Ozan (Eurasian Journal of Veterinary Sciences, 2022)
Aim: Reactive oxygen species (ROS) are produced during the metabolism of diethylnitrosamine (DEN) and phenobarbital (PB). Ellagic acid (EA) is a natural biologically active polyphenol with antioxidant activity. The present study was conducted to assess the preventive and protective capability of EA on DEN-PB-induced oxidative damage in rats. Materials and Methods: 60 Sprague-Dawley rats were assigned into 6 groups: Negative control, DEN, EA, DEN-PB (positive control), DEN-PB-EA (treatment), and EA-DEN-PB (pretreatment). 150 mg/kg DEN were administered to DEN, positive control, treatment and pretreatment groups. After two weeks, 500 ppm PB applied to positive control and treatment groups. 50 mg/kg/day EA were orally given to EA, and pretreatment groups for 8 weeks and treatment group was given for four weeks. After 8 weeks rats were sacrificed, liver and blood were subjected to biochemical evaluation. Results: DEN alone or with PB increased liver MDA levels significantly; however plasma MDA levels didn?t change. EA pretreatment decreased liver MDA levels (p<0.001). CAT activity did not change in the liver and erythrocytes of the positive control group. Liver CAT activity increased insignificantly in pretreatment and significantly in treatment group (p<0.05). SOD activity did not change in liver and erythrocytes of DEN and positive control groups. EA increased liver SOD activity significantly (p<0.001). DEN application alone or with PB decreased liver and blood GSH levels significantly (p<0.05), while EA application increased liver GSH levels in treatment (p<0.05). Blood GSH levels decreased significantly in treatment (p<0.001). Conclusion: It is considered that EA pretreatment could be more effective than EA treatment in DEN, PB induced oxidative stress in rats.